High serum levels of soluble interleukin-2 receptor (sIL2-R), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF) are associated with adverse clinical features and predict poor outcome in diffuse large B-cell lymphoma. (August 2017) - Dlouhy, Ivan; Filella, Xavier; Rovira, Jordina; Magnano, Laura; Rivas-Delgado, Alfredo; Baumann, Tycho; Martínez-Trillos, Alejandra; Balagué, Olga; Martínez, Antonio; González-Farre, Blanca; Karube, Kennosuke; Gine, Eva; et al.
Highlights: High serum IL6, IL2-R or TNF levels were associated with shorter survival in DLBCL. Early death strongly correlated with elevated cytokines. Serum cytokines add further survival information along with RIPI score. Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive lymphoma with heterogeneous outcomes. To improve accuracy of the international prognostic index score, new biological variables are being investigated. The aim of this study was to determine the prognostic significance of serum levels of different cytokines, namely soluble interleukin-2 receptor (sIL2-R), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF). We analyzed 197 de novo DLBCL patients (91 M/106 F; median age 66 years) treated with immunochemotherapy in a single institution. Serum cytokine determination was performed with ELISA, using the upper normal values as cut-offs. sIL-2R, IL-6 and TNF were elevated in 133, 130 and 144 cases, respectively. Elevation of each of these cytokines correlated with worse performance status, presence of B symptoms, advanced stage, elevated LDH and β2-microglobulin ( P <  0.03) and lower complete remission rate ( P <  0.001). Elevated levels of serum sIL-2R and TNF were significantly associated with shorter progression-free (PFS) and overall survival (OS), while elevated IL-6 only with shorter PFS. Early death (<4 months from diagnosis) strongly correlated with elevated cytokines. Determination of serum cytokines levels is simple and adds information regarding risk of early death, response to therapy, and outcome.